O contemporâneo en cena: literatura, estudos culturais, trauma e afetividade na trilogia de Antônio Torres - Silva, Amanda da (2011)
In this paper, we intend to reach the understanding of Antonio Torres writing, specifically in his trilogy – The Land (1976), O Cachorro e o Lobo (1997) and Pelo fundo da Agulha (2006) – novels that show the most common problems faced by part of Brazilian population, the mi-grations between regions and the disputes among the individuals who face this process, trying to see how the author gets the flow of the modern world, in order to represent, through his characters, the idea of instability before life, a characteristic of these post-modern times. At a first moment we analyze Antonio Torres’s narrative, by setting it into the present and seeking the particularities of each novel, which show different moments in the life of the character Totonhim. At a second moment, we highlight the spaces shown in Torres’s narrative. They reflect the present times, as well as its consequence, globalization. From the migration theme, the dislocation and the cultural boundaries in the contemporary context. At the last moment we get into subjective questions as trauma and affection, the first, coming from the psycho-logical consequences caused by and during dislocation, while the later comes from the ‘lost paradise’ nostalgia. By noticing a world that has lost its outlines becoming more and more difficult to find a reference. The literature then, becomes an important ally on the search for this new global condition understanding.